Tribological Properties of 3D Printed Materials in Total Knee Endoprosthesis - Varhanik, Matus; Sedlak, Josef; Studeny, Zbynek; Janigova, Patricia; Chromjakova, Felicita (Manufacturing Technology Journal, 2024)
The submitted paper deals with biotribological contact in total knee arthroplasty. The goal was to evaluate the influence of the metal component production technology on tribological parameters in defined environments. The reference sample was a standard available test ball made of the subject material, used in testing tribological properties by the "Ball on Pin" method. The preparation of the experiment consisted in the production of test disks from UHMWPE material and the production of a metal test component with a spherical surface. The condition of the experiment and the basis of this contribution is to compare the properties of conventionally produced metal material against 3D printing. Using the SLM method, a sample with a semi-spherical surface on a cylindrical shank was produced, which was subsequently ground and polished to reflect the characteristics of the standard supplied test ball. The last step was the production of a suitable fixture in order to fit the sample into the tribometer. The so-called dry friction of the heterogeneous Ti6Al4V-UHMWPE pair and the friction in a biological lubricating environment represented by bovine serum were evaluated. The evaluation of the contact surfaces took place using a profilometer and an electron microscope. The coefficient of friction was determined directly from the test device - tribometer.
Keywords: Biotribological properties; Friction of 3D printed materials; Ti6Al4V-UHMWPE contact